ANALISIS PEMBELAJARAN BERBASIS LITERASI MUATAN PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN PADA PELAKSANAAN KURIKULUM MERDEKA - Fitriyani, Fitriyani; Marto, Hasia; Nasriani, Nasriani; Insiano, Dewi Angraini (Universitas Tanjungpura, 2025)
This research is motivated by the low literacy skills of students in Indonesia and the lack of understanding of the importance of literacy in Civics learning, especially in the implementation of the Merdeka Curriculum. This curriculum demands a paradigm shift in learning, including Civics, by emphasising the development of holistic competencies. Literacy is important because it enables students to analyse information, think critically, and communicate effectively regarding civic issues. This research used a qualitative approach with a case study design, involving teachers and grade 1 students at SD Negeri Percontohan as research subjects. Data were collected through classroom observation, interviews with teachers and students, as well as document analysis such as lesson plans and teaching materials. The results showed that teachers have implemented various literacy-based learning strategies, such as the utilisation of various learning resources (books, picture stories, videos, and interactive games) and reading and writing activities that encourage students to explore the values of Pancasila. The implementation of these strategies had a positive impact on improving students' literacy skills, especially in terms of reading, writing, critical thinking and communication skills. However, this study also identified some challenges in implementing literacybased learning, such as limited learning resources relevant to students